2007
DOI: 10.1007/s00586-007-0408-9
|View full text |Cite
|
Sign up to set email alerts
|

PDGF, bFGF and IGF-I stimulate the proliferation of intervertebral disc cells in vitro via the activation of the ERK and Akt signaling pathways

Abstract: Intervertebral disc (IVD) degeneration is frequently characterized by increased cell proliferation, probably as a tissue regenerative response. Although many growth factors and their receptors have been shown to be expressed normally in the disc, and generally to be overexpressed during degeneration, not all of them have been thoroughly studied concerning their effects on IVD cell proliferation. In the present report, three potent mitogens, platelet-derived growth factor (PDGF), basic fibroblast growth factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
120
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 53 publications
11
120
1
1
Order By: Relevance
“…DNA synthesis in young and senescent fibroblasts was estimated after dual labeling with 5-bromo-2'-deoxyuridine (BrdU) and 4',6-diamino-2-phenylindole (DAPI) dihydrochoride, as previously described (23). Briefly, cells were plated sparsely on glass coverslips in DMEM containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA synthesis in young and senescent fibroblasts was estimated after dual labeling with 5-bromo-2'-deoxyuridine (BrdU) and 4',6-diamino-2-phenylindole (DAPI) dihydrochoride, as previously described (23). Briefly, cells were plated sparsely on glass coverslips in DMEM containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…For measuring the effect of conditioned media on cancer cell growth, A549 or H1299 cells were plated at a density of 8x10 3 cells/cm 2 , in DMEM containing 10% FBS. After 6 h the medium was changed to DMEM containing 1% FBS for another 24 h. Then, the conditioned media to be tested were added to the sparse cultures, diluted 1:1 with fresh DMEM containing 2% FBS along with [methyl-3 H]-thymidine (0.2 µCi/ml, 25 Ci/mmol) and after 24 h of thymidine incorporation was measured by scintillation counting, as previously described (23).…”
Section: Methodsmentioning
confidence: 99%
“…It has been extensively studied in the literature and is found to be involved in numerous cellular functions in various cell types, including angiogenesis, tumorigenesis, cell proliferation, differentiation, wound healing, limb formation, and tissue remodeling (Bodo et al, 2002;Bobick et al, 2007;Douwes Dekker et al, 2007;Kakudo et al, 2007;Kanayama et al, 2007;Pratsinis and Kletsas, 2007;Schmal et al, 2007;Choi et al, 2008). In chondrocytes, the role of bFGF as an important cell growth regulatorin the growth plate is already well established (Kilkenny and Hill, 1996).…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 99%
“…Additionally, Takahashi et al (14) revealed that the polymorphism 5A allele, which often occurs in the promoter region of the gene that regulates MMP-3 expression, was a possible risk factor for accelerated IDD in the elderly. In addition, Pratsinis et al (15) reported that platelet-derived growth factor, insulin-like growth factor-I and basic fibroblast growth factor could stimulate the proliferation of intervertebral disc cells via the activation of the extracellular-signal regulated kinase and Akt signaling pathways. By contrast, microRNAs (miRNAs) that can regulate RNA degradation or repression of translation have been identified as key regulators in numerous biological processes (16).…”
Section: Introductionmentioning
confidence: 99%